2020
DOI: 10.1152/ajpcell.00277.2020
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Wnt/Dickkopf1 signaling by mesenchymal vascular progenitor cells in the microvascular niche maintains distal lung structure and function

Abstract: The well described Wnt inhibitor Dickkopf-1 (DKK1) plays a role in angiogenesis as well as regulation of growth factor signaling cascades in pulmonary remodeling associated with chronic lung diseases including emphysema and fibrosis. However, the specific mechanisms by which DKK1 influences mesenchymal vascular progenitor (MVPC), endothelial and smooth muscle cells within the microvascular niche have not been elucidated. In this study, we show that knock down of DKK1 in Abcg2pos lung mouse adult tissue residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The most downregulated gene following ZNF827 knockdown is CKAP4 , which encodes the Cytoskeleton-associated protein 4. CKAP4, also known as cytoplasmic protein 63, is a transmembrane and endoplasmic reticulum protein acting as a receptor to several proteins such as tissue plasminogen activator 44 , Wnt inhibitor Dickkopf-1 45 or nexin 17 46 , with major implications in angiogenesis and SMC function. CKAP4 was recently found to regulate vascular SMC survival in the context of abdominal aortic aneurysm 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The most downregulated gene following ZNF827 knockdown is CKAP4 , which encodes the Cytoskeleton-associated protein 4. CKAP4, also known as cytoplasmic protein 63, is a transmembrane and endoplasmic reticulum protein acting as a receptor to several proteins such as tissue plasminogen activator 44 , Wnt inhibitor Dickkopf-1 45 or nexin 17 46 , with major implications in angiogenesis and SMC function. CKAP4 was recently found to regulate vascular SMC survival in the context of abdominal aortic aneurysm 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The main manifestations of the microvascular disease related to T2DM are diabetic retinopathy, diabetic nephropathy, and diabetic neuropathy [24] (Figure 2). The mechanisms that lead to vascular damage are multiple and involve various alterations in signaling pathways, including the Wnt pathway [13,25]. Table 1 shows some components of the Wnt pathway that are altered in the microvascular diseases in T2DM patients.…”
Section: Wnt Pathway and Microvascular Disease In Type 2 Diabetes Mel...mentioning
confidence: 99%
“…According to the most recent publications (Etc 2019; Xie et al, 2016), interstitial lung fibroblasts, pericytes, lipofibroblasts, mesothelial cells and LR-MSCs, whose roles within the alveolar lung niche are list in the legend within the figure, give rise to the myofibroblast population representing the key cells for the onset and progression of fibrosis. activation of Wnt in linage labeled ABCG2 positive pulmonary mesenchymal vascular progenitor cells (MVPC) drive microvascular dysfunction and exacerbated fibrosis (Summers et al, 2021). In 2011 Jun and collaborators demonstrated that treatment of mice with bleomycin led to the decrease of endogenous LR-MSCs population identified as H33342 low CD45 neg by flow cytometry and in vivo by immunostaining to detect the multidrug resistance transporter ATP binding cassette (ABCG2.)…”
Section: The Role Of Lung Resident Mesenchymal Stromal/stem Cells In Lung Homeostasis Injury and Repairmentioning
confidence: 99%
“…Cao et al found that inhibition of the Shh-Wnt pathway in the bleomycin mouse model prevented LR-MSCs from differentiating into myofibroblasts and reduced lung fibrosis ( Cao et al, 2018 ). Summers et al, further report in the same model that genetic activation of Wnt in linage labeled ABCG2 positive pulmonary mesenchymal vascular progenitor cells (MVPC) drive microvascular dysfunction and exacerbated fibrosis ( Summers et al, 2021 ). In 2011 Jun and collaborators demonstrated that treatment of mice with bleomycin led to the decrease of endogenous LR-MSCs population identified as H33342 low CD45 neg by flow cytometry and in vivo by immunostaining to detect the multidrug resistance transporter ATP binding cassette (ABCG2.)…”
Section: The Role Of Lung Resident Mesenchymal Stromal/stem Cells In Lung Homeostasis Injury and Repairmentioning
confidence: 99%